2001
DOI: 10.1079/bjn2000284
|View full text |Cite
|
Sign up to set email alerts
|

A European carotenoid database to assess carotenoid intakes and its use in a five-country comparative study

Abstract: A food frequency questionnaire (FFQ) and carotenoid database with information on a-and bcarotene, lutein, lycopene and b-cryptoxanthin was prepared and used to compare the carotenoid intakes in five European countries: UK, Republic of Ireland, Spain, France and The Netherlands. Eighty, age-(25±45 years) and sex-matched volunteers were recruited in each of the five countries. A FFQ and carotenoid database was prepared of the most commonly consumed carotenoid rich foods in the participating countries and the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
230
5
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(260 citation statements)
references
References 29 publications
23
230
5
2
Order By: Relevance
“…Similarly, plasma b-cryptoxanthin level positively associated with fruits (especially citrus variety) intake. These findings are consistent with the results from major databases, which contain information on the main sources of carotenoids in foods (O'Neill et al, 2001;Garcia-Closas et al, 2004), suggesting that there are good correlations between carotenoid intake from foods and the respective carotenoid levels in plasma, findings supported by other epidemiological/ intervention studies (Trichopoulou et al, 2003;Brevik et al, 2004;Jansen et al, 2004). Epidemiological studies have shown negative associations between plasma level of several carotenoids and the risk of chronic degenerative diseases including cancers (Sato et al, 2002;Abnet et al, 2003;Steck-Scott et al, 2004), stroke (Hak et al, 2004) and macular degeneration (Gale et al, 2003).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, plasma b-cryptoxanthin level positively associated with fruits (especially citrus variety) intake. These findings are consistent with the results from major databases, which contain information on the main sources of carotenoids in foods (O'Neill et al, 2001;Garcia-Closas et al, 2004), suggesting that there are good correlations between carotenoid intake from foods and the respective carotenoid levels in plasma, findings supported by other epidemiological/ intervention studies (Trichopoulou et al, 2003;Brevik et al, 2004;Jansen et al, 2004). Epidemiological studies have shown negative associations between plasma level of several carotenoids and the risk of chronic degenerative diseases including cancers (Sato et al, 2002;Abnet et al, 2003;Steck-Scott et al, 2004), stroke (Hak et al, 2004) and macular degeneration (Gale et al, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…The increased plasma carotenoids, resulting mainly from the increased vegetables intake in vegetarians could also reflect elevated levels of 'other' phytochemicals in blood/body, which have not been measured in this study, including polyphenols, phyto-oestrogens and organosulfer compounds that are thought to have antioxidant as well as other biologically important properties (Kris-Etherton et al, 2002). It should be noted that the plasma levels of b-cryptoxanthin were similar in the two diet groups, which was most likely to be owing to similar intakes of fruits between the vegetarians and omnivores, as fruits such as oranges are the major dietary sources of this carotenoid (O'Neill et al, 2001).…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, the true intake of phytoestrogens and lycopene in our population may be underestimated. Overall, intake of phytoestrogens and lycopene in our study is relatively low, but comparable to that observed in many other Western populations [44,[58][59][60]. Within this low range, limited variation in phytoestrogens and related foods, and lycopene and tomato intake might explain why we did not observe an association with IGF-I and IGFBP-3.…”
Section: Discussionsupporting
confidence: 84%
“…Plasma concentrations of lycopene also increased but this increase did not reach a level of statistical significance. Additional lycopene would mainly come from the tomato soup, which would provide about 1.2 mg lycopene per day, based on the tomato content (O'Neill et al, 2001). The lack of change in plasma levels of retinol and a-tocopherol when fruit and vegetable intake was increased agrees with previous intervention studies.…”
Section: Discussionsupporting
confidence: 82%